Toxicity of formalin to prawn (Penaeus monodon) mysis 2 larvae. - Gulmatico, Ma. Vanessa
Toxicity of formalin to prawn (Penaeus monodon) mysis larvae was tested using static bioassay. Twelve and twenty four hour LC50 were 15.0 and 10.9 pmm, respectively. The prawn myses exposed to 5 pmm could tolerate the chemical after 24 hours of exposure while concentrations of 20 and 25 ppm produced 100 mortality. Abnormal behavior exhibited by the larvae include disorientation and sudden jerky swimming movements, increased swimming activity, reddening of the body and settling down at the bottom of the containers.